Intermolecular Rhodium(II)‐Catalyzed Allylic C(sp3)–H Amination of Cyclic Enamides. Issue 3 (19th January 2018) - Rey‐Rodriguez, Romain; Jestin, Grégory; Gandon, Vincent; Grelier, Gwendal; Retailleau, Pascal; Darses, Benjamin; Dauban, Philippe; Gillaizeau, Isabelle
Abstract: The intermolecular rhodium(II)‐catalyzed C( sp 3 )–H amination of enamides gives access to new 4‐aminopiperidine derivatives that are useful building blocks in medicinal chemistry. This efficient transformation proceeds at room temperature with complete regio‐ and chemoselectivity in favor of the allylic C( sp 3 )–H bond, and has a broad functional group tolerance. In addition, the matched combination of the chiral complex Rh2 ( S ‐nta)4 [nta=( S )‐ N ‐1, 8‐naphthoylalanine] with an optically pure ( S )‐sulfonimidamide allows the isolation of allylic amines with excellent stereocontrol. Abstract :